2019
DOI: 10.18203/2319-2003.ijbcp20193183
|View full text |Cite
|
Sign up to set email alerts
|

A study on pattern of adverse drug reaction in an adverse drug reaction monitoring centre of a tertiary care hospital in South Kerala, India

Abstract: Background: Adverse drug reactions (ADR) are rated as fifth leading cause of death and accounts for approximately 5% of all hospital admissions. Under reporting of ADR from healthcare professional is considered as the contributing factor for increased morbidity and mortality. India has taken well appreciated step to launch Pharmacovigilance Programme of India (PvPI) to safeguard heath care of Indian population. This study looks into the detailed analysis of ADR reported to adverse drug reaction monitoring cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…ADR/AE could be considered as a differential diagnosis of heterogenetic conditions, as it is difficult to diagnose. 12 In general practice unexpected hospital admissions around 6% and consultations around 3% and were found to be due to ADRs/AEs. 13 In the present study we have encouraged all the HCPs and direct consumer or patient caretakers for reporting ADRs/AEs in order to strengthen the patient safety contribution from each individual which plays a major role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADR/AE could be considered as a differential diagnosis of heterogenetic conditions, as it is difficult to diagnose. 12 In general practice unexpected hospital admissions around 6% and consultations around 3% and were found to be due to ADRs/AEs. 13 In the present study we have encouraged all the HCPs and direct consumer or patient caretakers for reporting ADRs/AEs in order to strengthen the patient safety contribution from each individual which plays a major role.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,18,24,25 Considering the outcome parameter the end result of the reported cases in the indexed period are mostly recovered followed by recovering, not recovered and fortunately only one case of fatal was reported which where compared with similar to study conducted in India while studies done by Sneha et al and Hemavathy G et al reported cases with recovering outcome parameter were higher then recovered. 5,7,12,26,27 In regards to the causality assessment it is to determine the relatedness or the likelihood of the drug (s) with reaction (s) establishing the reasonable time relationship and considering the comorbid factors. In the present study there is no much significant difference was observed between probable and possible criteria.…”
Section: Discussionmentioning
confidence: 99%